Leakage and wear characteristics of finger seal in hot/cold state for aero-engine. (November 2018) - Guoqing, Li; Qian, Zhang; Lei, Guo; Qiangpeng, Yu; Gang, Xu; Junqiang, Zhu
Abstract: Experimental investigation has been done to approach the leakage and wear characteristics of finger seal in hot/cold state. The High-speed Sealing Test Rig was used in the study. Leakage measurements were done in terms of different working parameters. The pressure ratio changed from 1.1 to 1.8 and the rotating speed varied from 0 to 5000 rpm. The temperature altered from 283 K to 433 K to achieve the cold state and hot state, respectively. Two groups of durability tests were carried out in hot/cold state, separately. Each durability test lasted 300 h with two finger seals. An accurate optical measuring instrument was applied to record the wear growth of the finger seals. Results showed that the flow factor monotonously increases with the pressure ratio and decreases with the rotating speed. An attractive feature is firstly captured that the finger seal with double-laminate achieves lower leakage in cold state while the finger seal with triple-laminate behaves better in hot state. Full life-cycle theory was applied to analyse the wear of the finger seal. The wear growth curve exhibits a rule of SPSP (Sharp Wear, Progressive Wear, Stable Wear and Permanent Wear). Of particular interest is the wear comparison between hot state and cold state, which is firstly discussed in the study and shows that finger seals operating in hot state generate obviously more wear than those in cold state. Highlights: Finger seal operating in hot state generates more wear. Four periods of wear growth curve are divided by Full Life-cycle analysis. Leakages are achieved in different pressure ratio, temperature, rotating speed and finger laminates. Finger seal with double-laminate achieves lower leakage in cold state while the triple-laminate behaves better in hot state.